Effect of spatial heterogeneity on Zooplankton diversity: a multi-scale habitat approximation in a floodplain lake - Chaparro, Griselda Noemí (2013)
Environmental heterogeneity is an essential quality of ecosystems as it has important implications in community structure. Macrophytes are a main component of environmental heterogeneity in floodplain lakes, and their dynamics are highly influenced by water level changes. In this context, we analysed at different spatial scales the relationship among hydrological variations, environmental heterogeneity associated to macrophytes and zooplankton regional diversity (γ diversity) in a South American floodplain lake adjacent to the Paraná River, and we also compared the local zooplankton diversity (α diversity) among the different environments that comprised the lake heterogeneity. At very low waters, the environmental heterogeneity was reduced as the lake was mainly limited to open water areas with low zooplankton diversity. At high waters, the profuse vegetation development (emergent and free-floating), in mixed or homogeneous patches, determined a higher lake environmental heterogeneity with enhanced regional zooplankton diversity; littoral species increased over limnetic ones. Zooplankton α diversity was higher in environments with free-floating macrophytes than in those without these plants. The structural complexity in the water column provided by plant roots would be closely related to the enhanced diversity found under free-floating mats. This study contributes to the knowledge on the effects of strong water level variations on environmental heterogeneity, which is strongly associated to macrophytes and on zooplankton diversity, and highlights the role of free-floating plants as diversity hosts and ‘key structures’ in floodplain lakes.